2011
DOI: 10.1002/ird.644
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Water Relations of Cotton–maize Cropping Sequence Under Deficit Irrigation Using Drip System

Abstract: The assessment of water use efficiency and crop performance of cotton–maize cropping sequence under deficit irrigation has not been thoroughly studied in India. Field experiments were conducted at the Agricultural College and Research Institute, Coimbatore, during 2007–2009 to study the effect of deficit irrigation practices through a drip irrigation system on crop productivity, and the water use efficiency of cotton–maize cropping sequence. Experimental treatments comprised of six irrigation levels (full and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Because the 2.5 and 5 mm d −1 irrigation capacities provided >70% of estimated seasonal crop water demand and differed by ∼20% most years, the resulting crop water deficit stress was insufficient for significant yield differences between irrigation capacities. Similarly, Sampathkumar et al (2012) reported no significant yield difference between cotton irrigated at 80 or 100% of the crop evapotranspiration requirement.…”
Section: Resultsmentioning
confidence: 96%
“…Because the 2.5 and 5 mm d −1 irrigation capacities provided >70% of estimated seasonal crop water demand and differed by ∼20% most years, the resulting crop water deficit stress was insufficient for significant yield differences between irrigation capacities. Similarly, Sampathkumar et al (2012) reported no significant yield difference between cotton irrigated at 80 or 100% of the crop evapotranspiration requirement.…”
Section: Resultsmentioning
confidence: 96%